New methods and equipment of decametric radio astronomy for continuum observation at the UTR-2 radio telescope - Sidorchuk, K.M.; Konovalenko, A.A.; Rucker, H.O.; Lecacheux, A.; Denis, L.; Sidorchuk, M.A.; Rashkovsky, S.L.; Dorovsky, V.V.; Zakharenko, V.V. (Кинематика и физика небесных тел, 2005)
At present time the modernization of the giant decametric radio telescope UTR-2 is under way. New back-end facilities and methods which open up new possibilities for radio astronomical observations are developed. Some equipment was made in cooperation with Austrian and French radio astronomers. Current back-end facilities and methods used at the UTR-2 radio telescope are described and compared with former traditional methods, equipment and their characteristics. Some prospects regarding current progress in developing new generation of back-end facilities are also discussed. The main focus of the presentation is the observation methods and equipment applied at the UTR-2 radio telescope for the investigation of continuum radio sources: Galactic background, discrete sources (preparation for the catalogue of sources in the whole Northern Sky), SNR, HII regions. Some results of using the new back-end facilities (such as Digital Spectral Polarimeter) and processing methods are presented.